PELATIHAN KESELAMATAN BAGI ANAK BUAH KAPAL - Lasse, D; Fatimah, Fatimah (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2016)
Training program is one of the company’s way to get and select qualified human resources based on the company’s needs and wants. To find out the relationship between safety training on the ship MV. Hilir Mas and the operational performance of PT. Tempura Emas shipmen, the researcher is using two methods which are qualitative method (collecting data from field and library research) and quantitative method ( data taken from the questionnaire response and data analysis using Likert Scale. The result shows that there is a significant and positive relationship between the operational performance of PT. Tempura Emas shipmen and safety training on the ship MV. Hilir Mas.